FONDASI KEMANANAN SIBER UNTUK LAYANAN PEMERINTAH - Witjaksono, Dhanang Ksatrio; Kriswibowo, Arimurti (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
The use of the internet in the current government environment continues to grow. The increasingly complex use of the internet can cause vulnerabilities to cyber attacks in information security, which include aspects of confidentiality, integrity, and service availability, so that it can disrupt the performance of public service delivery. The systematic literature review research method was carried out because of the large amount of information and data regarding cyber security strategies. This can be traced through various information in books, scientific journals, newspapers, magazines, as well as sources of information from web pages/websites via the internet. This method is important in analyzing the concept of cyber security strategy in Indonesia. The obstacles that the government has are expired devices that are still used on local government networks, which may not have the latest updates, security devices such as antiviruses have expired, human resources have not fully supported this cybersecurity. Indonesia needs policies that regulate all elements related to cyber security. This infrastructure standard must comply with international standards for dealing with cyber warfare.